PERCEIVED EASE OF USE AND PERCEIVED USEFULNESS ON THE INTENTION TO USE E-TICKETING FOOTBALL - Saddam Aldiva Mahardika; Yohanes Suhari (LPPM STMIK Pringsewu, 2023)
Currently, the sphere of sports is continuously expanding in Indonesia. E-ticketing has made it possible for fans to quickly and easily purchase tickets to soccer matches thanks to advances in technology and information. Some studies have found that the ability to distribute tickets rapidly and efficiently is one of the e-greatest ticketing benefits. The goal of this study is to evaluate how soccer fans' perceptions of the ease and advantages of ticket purchasing influence their willingness to make those purchases. Subjects in this study are the 120 football fans who regularly attend PSIS Semarang games in International Stadium Jatidiri Semarang. This study also has a quantitative component. The analysis that is used is a multivariate regression. This study shows that a minimal number of soccer fans still prefer to purchase tickets online. In addition, the study found that (1) ease of usei has a positive impact on perceived usefulness of e-ticketing, (2) ease of use has no effect on the intention to use e-ticketing, and (3) perceived usefulness of e-ticketing have a positive impact on the intention to use e-ticketing.